2021
DOI: 10.21608/aasj.2021.77678.1065
|View full text |Cite
|
Sign up to set email alerts
|

Effect of macroalgae and yeast culture on body performance, blood metabolites, ruminal fermentation and digestibility coefficients of Ossimi lambs

Abstract: This study was carried out to evaluate the effect of macroalgae (Halimeda opuntia) and yeast culture (saccharomyces cerevisiae) as feed additives on body performance, some blood plasma constituents, some rumen parameters and nutrients digestibility of growing lambs. Fifteen Ossimi lambs 5-6 months old and 25.51 ± 2 kg live body weight were randomly divided into three equal groups (5 animals each). Control group (CON) was fed the basal diet and other two treatment groups were fed the same basal diet, supplement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 20 publications
(26 reference statements)
0
0
0
Order By: Relevance
“…Serum TP, which mainly includes ALB and globulin, is an indicator of the nutritional status of animal ( Doornenbal et al, 1988 ). Abu El-Kassim et al (2021) reported that dietary yeast supplementation increased blood plasma ALB concentrations in Ossimi lambs, which was consistent with the results of the current study. This indicates that the serum concentrations of ALB were affected by YC and pure chemical combination supplementation, possibly resulting from the improvement in nutrient digestibility in the feed.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Serum TP, which mainly includes ALB and globulin, is an indicator of the nutritional status of animal ( Doornenbal et al, 1988 ). Abu El-Kassim et al (2021) reported that dietary yeast supplementation increased blood plasma ALB concentrations in Ossimi lambs, which was consistent with the results of the current study. This indicates that the serum concentrations of ALB were affected by YC and pure chemical combination supplementation, possibly resulting from the improvement in nutrient digestibility in the feed.…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, Soren et al (2013) reported that the ADG was not significantly influenced by YC supplementation in lambs. Abu El-Kassim et al (2021) also reported that YC improved the ADG of lambs, although the increase did not reach statistical significance, consistent with the findings of the present study. In this study, supplementation with YC and pure chemical combinations improved the ADG of lambs, which may be because of the presence of mannan and 5-hydroxytryptophan in both YC and pure chemical combinations.…”
Section: Discussionsupporting
confidence: 90%
“…Where: ctrl = Diet 2 (17% hemicellulose); L = diet 2 with low yeast culture; H = diet 2 with high yeast culture; l = diet 2 with low oxalic acid; h = diet 2 with high oxalic acid; Ll = diet 2 with low yeast culture and low oxalic acid; Lh = diet 2 with low yeast culture and high oxalic acid; Hl = diet 2 with high yeast culture and low oxalic acid; and Hh = diet 2 with high yeast culture and high oxalic acid. (39,40). Nevertheless, studies examining the impact of OA have shown that it does not have a statistically significant influence on rumen pH (41).…”
Section: Rumen Fermentation Parameters 421 Ruminal Phmentioning
confidence: 99%